Self-monitored Nd-doped MoSe2 nanosheets with near-infrared luminescent sensing for photothermal therapy - Congcong Wang; Yu Meng; Zewen Su; Junqiang Dong; Yanbang Lian; Youqiang Huang; Yinyan Li; Shiqing Xu; Gongxun Bai (Journal of Materiomics, 2024)
The acquisition of real-time temperature monitoring during photothermal therapy is significant to prevent unnecessary damage to healthy tissues. However, owing to complexity and diverse factors in microenvironment of cells, there still remain considerable challenges in achieving noninvasive temperature measurement and manipulation in therapeutic process. Herein, biocompatible Nd-doped MoSe2 nanosheets have been developed on the premise of excellent photothermal effect, which manifest desirable photoluminescence and distinct temperature self-monitored capability in near-infrared I and II bio-windows. Based on thermally coupled energy levels of Nd ions, the real-time monitoring on temperature changes in intracellular environment can be realized which provide instant temperature feedbacks to avoid side effects from hyperthermia. Exclusive of detrimental elements such as F and Pb, the objective nanosheets manifest satisfactory biosafety and can induce effective tumor ablation under near-infrared irradiation with photothermal conversion efficiency up to 40.8%, providing an innovative vision for developing more precisely and safely photothermal approaches.